Nanosecond formation of diamond and lonsdaleite by shock compression of graphite - D. Kraus (Nature Portfolio, 2016)
Shock synthesis of diamond and even harder carbon polymorphs from graphite is of great interest for science and technology. Here, the authors present unprecedented in situmeasurements of the structural changes, showing ultrafast formation of diamond and, at higher pressures, evidence for a pure lonsdaleite structure.